APPLICATIONS OF COMPUTER GRAPHICS - Achilov Murodjon Ashirkulovich; Makhmudov Jasurbek Ilhom son (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract : What does the concept of information society mean? This is a society in which the majority of workers are busy with the production, storage, processing and implementation of information. What is computer graphics (machine graphics)? Machine graphics means creation, storage, processing of volumetric models of objects and their representation using EHMs.